Election and Stock Market - Rahima Br Purba; Junawan (Yayasan Multidimensi Kreatif, 2025)
The general election (Pemilu) is a political event that significantly impacts the economy, including the stock market. Political uncertainty during the election period can influence investor behavior, market volatility, and stock trading patterns. This study aims to analyze stock trading trends on the Indonesia Stock Exchange (IDX) during election seasons, identify specific patterns in stock transactions during elections compared to normal periods, and examine the factors influencing changes in stock transactions during elections. The research method used in this study is descriptive analysis with a secondary data approach obtained from the Indonesia Stock Exchange (IDX), the Financial Services Authority (OJK), and various academic sources and scientific journals. The results indicate that during the election period, market volatility increases, particularly in the infrastructure, banking, and property sectors, which experience price surges due to expectations of government policies supporting investment and development. Conversely, the energy and industrial sectors experience high fluctuations due to uncertainties surrounding policies that will be adopted by the new administration. The key factors influencing stock transactions during elections include political uncertainty, which leads investors to favor defensive stocks; government economic policies, where campaign promises and fiscal policy plans affect stock price movements; and market sentiment, which is shaped by survey results and polling of competing candidates. The study concludes that elections have a significant impact on stock trading patterns, leading to increased volatility and a tendency for investors to shift their investment portfolios to safer sectors. Therefore, investors are advised to diversify their investments and consider political factors in their investment strategies. Stricter regulations and greater transparency from capital market authorities are also necessary to maintain market stability during election periods..